2008
DOI: 10.1177/0148607108316190
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing Candida Infection After Percutaneous Endoscopic Gastrostomy: A Fatal and Rare Complication

Abstract: Gastrostomy site infections following percutaneous endoscopic gastrostomy (PEG) are the most common complication after PEG placement. Recent meta‐analyses were able to show that PEG site infections can be reduced significantly with a systemic antimicrobial prophylaxis. This mostly cephalosporin‐ or penicillin‐based prophylaxis does not cover fungal infections. Although Candida skin infections after PEG placement are rarely described, a mucosal colonization or infection of the upper GI tract with Candida specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Seit der Einführung der PEG ist die Zahl ihrer Anwendungen ex ponenziell gestiegen, sodass die se Proze dur beispielsweise in Deutschland mehr als 140.000mal/Jahr durchgeführt wird [68,69]. Unter Beachtung der Indikatio nen und Kontraindikationen (.…”
Section: Perkutane Sondenunclassified
“…Seit der Einführung der PEG ist die Zahl ihrer Anwendungen ex ponenziell gestiegen, sodass die se Proze dur beispielsweise in Deutschland mehr als 140.000mal/Jahr durchgeführt wird [68,69]. Unter Beachtung der Indikatio nen und Kontraindikationen (.…”
Section: Perkutane Sondenunclassified
“…C. parapsilosis is a common cause of skin infection; however, NSTI caused by any Candida species is very rare . Reports are limited regarding necrosis related to C. parapsilosis .…”
Section: Discussionmentioning
confidence: 99%
“…One study reported a mortality outcome of 38% in a delayed treatment cohort, compared with 4.2% in early intervention (7). C. parapsilosis is a common cause of skin infection; however, NSTI caused by any Candida species is very rare (2,8,9). Reports are limited regarding necrosis related to C. parapsilosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a theoretical, but unproven benefit of stopping all acidreducing agents in the week before surgery. Fungal prophylaxis is particularly indicated for children who have been on antibiotics prior to surgery [16].…”
Section: Percutaneous Gastrostomiesmentioning
confidence: 99%